The Metaphysics of Sparse Properties and Deep Resemblance Nominalism - Demirli, Sun (Problemos, 2025)
This paper introduces Deep Resemblance Nominalism (DRN) as a novel approach within the framework of resemblance nominalism and compares it to other forms of nominalism, including Rodriguez-Pereyra’s Resemblance Nominalism (RN). DRN departs from RN in two significant ways. The first major difference lies in the formal properties of the resemblance relation. In RN, resemblance is treated as a two-place relation that holds between pairs of particulars. In contrast, DRN interprets resemblance as a plural relation, connecting a particular to a plurality of particulars, rather than as a two-place relation between individual pairs of particulars. The second key difference lies in how the resemblance relation is understood. While RN characterizes resemblance as an internal relation grounded solely in the existence of resembling particulars, DRN treats resemblance as an irreducible relation that exists among particulars, rather than an internal one. I will argue that DRN offers a superior nominalist approach, not only when compared to RN but also to the other nominalist alternatives discussed in this paper.
Keywords: resemblance nominalism; mereological nominalism; fundamentality; class nominalism; primitives; primitive modality